Konsepsi Manajemen Mutu dalam Pendidikan - Abdul Hadi (MODELING: Jurnal Program Studi PGMI, 2018)
This journal focuses on the quality of professionally managed educational institutions through integrated quality management. Educational institutions as producer services sector should pay attention to quality; quality of managerial and academic aspects. These two aspects can be achieved through the application of the concept of total quality management (TQM). TQM is a management concept that places all insan (civitass academica) of higher education institutions as individuals who have responsibility for quality in accordance with their duties and functions. TQM is an approach to doing business that seeks to maximize the competitiveness of institutions through continuous improvement of products, services, people, processes and the environment. TQM is the starting point for improving quality that will be under the jargon of "do the right thing, first time, and every time". Quality Management is part of management that aims to achieve Quality objectives through planning, monitoring, assuring and improving Quality. Involving all members of the organization brings us closer to Total Quality Management (TQM). Efficient Total Quality management system within the organization can facilitate rapidly challenges in the market. Total quality management embodies target and mission in youth education. TQM improves the quality of management and quality of work in educational institutions in general. Important points for educational improvement are scientific and technological development, social change and organizational change. The efficiency and success of education depends not only on quantity but also on quality. The indicators system The quality of education, as well as the criteria associated with the Quality indicators help schools to identify key areas of their activities - their own advantages, disadvantages and opportunities.